Diagnosis and Treatment of Leishmaniasis: Clinical Practice Guidelines by the Infectious Diseases Society of America (IDSA) and the American Society of Tropical Medicine and Hygiene (ASTMH). (7th December 2016) - Aronson, Naomi; Herwaldt, Barbara L; Libman, Michael; Pearson, Richard; Lopez-Velez, Rogelio; Weina, Peter; Carvalho, Edgar M; Ephros, Moshe; Jeronimo, Selma; Magill, Alan
Abstract: It is important to realize that leishmaniasis guidelines cannot always account for individual variation among patients. They are not intended to supplant physician judgment with respect to particular patients or special clinical situations. The IDSA and ASTMH consider adherence to these guidelines to be voluntary, with the ultimate determinations regarding their application to be made by the physician in the light of each patient's individual circumstances.